2020
DOI: 10.1186/s13068-020-01787-9
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of glucose assimilation in Auxenochlorella protothecoides by light

Abstract: Background The yield of microalgae biomass is the key to affect the accumulation of fatty acids. A few microalgae can assimilate organic carbon to improve biomass yield. In mixotrophic cultivation, microalgae can use organic carbon source and light energy simultaneously. The preference of the main energy source by microalgae determines the biomass yield. Auxenochlorella protothecoides is an oleaginous mixotrophic microalga that can efficiently assimilate glucose and accumulate a large amount of biomass and fat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 48 publications
3
3
0
Order By: Relevance
“…The lower growth rates of illuminated cells were most probably due to a potential inhibition effect of light on A. protothecoides grown mixotrophycally. As was reported by Xiao et al [33], the proteomics analysis of A. protothecoides cultivated in glucose revealed that light had an apparent restrictive effect on the metabolic process of organic carbon assimilation. In addition, it was demonstrated here that the mixotrophic conditions also affected the photosynthetic process and the photosynthetic apparatus heterogeneity of A. protothecoides.…”
Section: Mixotrophic Conditionssupporting
confidence: 64%
“…The lower growth rates of illuminated cells were most probably due to a potential inhibition effect of light on A. protothecoides grown mixotrophycally. As was reported by Xiao et al [33], the proteomics analysis of A. protothecoides cultivated in glucose revealed that light had an apparent restrictive effect on the metabolic process of organic carbon assimilation. In addition, it was demonstrated here that the mixotrophic conditions also affected the photosynthetic process and the photosynthetic apparatus heterogeneity of A. protothecoides.…”
Section: Mixotrophic Conditionssupporting
confidence: 64%
“…Inhibition of the substrate assimilation in the presence of light has been also reported from Xiao et al [ 31 ], when A. protothecoides was cultivated mixotrophically in a continuous system utilizing glucose instead of glycerol. In that case, glucose metabolism was also found to be restricted from the presence of light leading to limited biomass and lipids production.…”
Section: Resultssupporting
confidence: 62%
“…Light seems to have a potential inhibitory effect on A. protothecoides when grown mixotrophically, suggesting that A. protothecoides is not favored by the mixotrophic conditions, probably due to a combination of reduced organic carbon assimilation and lower photosynthetic performance. Inhibition of the substrate assimilation in the presence of light has been also reported from Xiao et al [31], when A. protothecoides was cultivated mixotrophically in a continuous system utilizing glucose instead of glycerol. In that case, glucose metabolism was also found to be restricted from the presence of light leading to limited biomass and lipids production.…”
Section: Heterotrophic Growth 30 G/l Glycerolsupporting
confidence: 66%
“…Microalgae (eukaryotic and prokaryotic cyanobacteria) are a large group of photoautotrophic organisms, as well as organisms capable of heterotrophic, mixotrophic, and photoheterotrophic existence [1,2]. They are adapted to life in a variety of habitats and produce biomass containing a wide variety of compounds that can be used in the food, pharmaceutical, and cosmetic industries, and for the production of biofuels, etc.…”
Section: Introductionmentioning
confidence: 99%